Mode Choice and Spatial Distribution of Coal Transport in Jambi, Indonesia - Nugroho, Nurman; Priyanto, Sigit; Triatmodjo, Bambang (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
Coal is an important commodity for Jambi Province. Based on data from the Central Bureau of Statistics, in the first quarter of 2022, the value of coal exports reached 10.75% of the total export value. Apart from being exported, coal commodity is also used for domestic purposes. The transport used at this time is only through public roads. The use of these routes results in many problems such as traffic accidents, congestion, and social conflicts. Therefore, the number of vehicles allowed to pass on public roads is limited. This has resulted in the production target plan not being achieved, only 17.3 million tonnes out of 40 million tonnes in 2022. Hence the need for other routes for transport such as rivers, special roads, and railways. This research is intended to analyse coal transport trips using trucks, barges and railways. This research discusses the closest route, mode selection, and transport costs based on the distance travelled and the travel time of each mode. The search for the closest travel route is done by spatial analysis with Network Analyst on ArcGIS. Mode choice was analysed using the multinomial logit method. Meanwhile, transport costs are calculated based on the principle of generalised cost. Modelling results on the selection of mode, during the rainy season the most efficient mode is barging with a selected probability of 44%, while rail 28% and transport by truck 27%. During the dry season, the probability of transport by railway is 93%, barge 4% and truck 3%. The results indicate that the most efficient mode during the rainy season is barging and during the dry season transport by railway.